Towards Sustainable Conventional Indian Houses: Linking Embodied Water-Energy Nexus to Pro-locals’ Architecture, Construction and Regulatory Reforms with Lifecycle Assessment and Scenarios Methods - Anoop Kumar Sharma; Prabhjot Singh Chani; Atul Anand Jha (Journal of Sustainable Development of Energy, Water and Environment Systems, 2025)

(untitled)
Real-world insights to conserve water in constructions without overshooting embodied energy meet sustainable development goal 12, specifically in the current thirsty world. The study aims to outline conclusive strategies to conserve embodied water and embodied energy, together with regulatory insights. Following the International Organization for Standardization’s 14046 and 14044 frameworks, the experiment accounts for cradle-to-gate lifecycle assessment, taking Jammu’s conventional houses in India as cases. Observing top-impacting embodied water materials differ from embodied energy ones, the experiment delves into the appraisal of ‘threats’ and ‘opportunities’ in locals’ preferences using the scenario manager technique. Not only was the embodied water and embodied energy offsetting by almost 30% achieved, but also, the flexible scenarios suiting economically diverse users have significant pragmatic worth. While the recommendations base is the embodied water-energy nexus and retains societal interests; indeed, the methodology and study’s implications are global and replicable. The experiment meets the three pillars of sustainability and thereby remarkably boosts the sustainable building practice.